1998
DOI: 10.3354/ame016143
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic metabolism in a forest stream sediment: surface versus subsurface zones

Abstract: The heterotrophic metabolism of a forest stream sediment was studied during leaf fall, immediately after a flood that completely scoured and homogenized the first 10 to 12 cm of sediment. After this event, differences were found between the surface sediment (0 to 3 cm depth) and the subsurface sediment (7 to 10 cm depth). Higher extracellular enzymatic and respiratory activities were measured in the surface than in the subsurface sediment. The higher heterotrophic activity was related to the higher quantity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 21 publications
3
30
0
1
Order By: Relevance
“…Microbial biomass was comparable to reports from previous studies of streambed sediments (6,12,63), and chlorophyll a concentrations were also within ranges previously reported (31,58). These previous studies found environmental and physical factors that correlated with microbial and autotrophic biomass levels.…”
Section: Vol 77 2011 Bedrock Influences Microbial Communities In Stsupporting
confidence: 78%
“…Microbial biomass was comparable to reports from previous studies of streambed sediments (6,12,63), and chlorophyll a concentrations were also within ranges previously reported (31,58). These previous studies found environmental and physical factors that correlated with microbial and autotrophic biomass levels.…”
Section: Vol 77 2011 Bedrock Influences Microbial Communities In Stsupporting
confidence: 78%
“…For example, during the present study, the annual rainfall varied between 855 mm in 1994 and 1660 mm in 1996. Alders (Alnus glutinosa) dominate the riparian vegetation and leaf fall is concentrated into a short period (20-30 days) in October when the particulate organic matter transported in the stream can increase by up to 8-10 mg l -1 (Romaní et al, 1998). The stream channel is 2.5 m wide and is characterised by step-pools with large pebbles and boulders.…”
Section: Introductionmentioning
confidence: 99%
“…The storm flow caused scouring and homogenisation of the hyporheic sediments, reduced the particulate organic matter (POM H ) from 52 to 4.8 mg AFDW g -1 (Fig. 6a) and decreased the hyporheic and benthic microbial activity (Romaní et al, 1998).…”
Section: (2) : Ammoniummentioning
confidence: 99%
“…On the other hand, hyporheic habitats are important storage zones for organic carbon (Leichtfried 1991, Bretschko & Moser 1993 and are generally characterized by sharp physical and chemical gradients (Hendricks & White 1995, Fraser & Williams 1998, thus enabling a broad spectrum of metabolic pathways to occur within small spatial scales. As a consequence, hyporheic habitats are often hot spots in productivity and diversity of organisms (Pusch et al 1998) and may contribute substantially to the energy flow through the lotic system (Jones & Holmes 1996, Naegeli & Uehlinger 1997, Romaní et al 1998). …”
Section: Introductionmentioning
confidence: 99%